2018
DOI: 10.1016/j.jaac.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Alcohol Initiation and Use During Adolescence: The Role of Stress and Amygdala Reactivity

Abstract: Adolescents on a trajectory of early alcohol use initiation have higher levels of stress, have increased threat-related amygdala activity, are more likely to consume a full standard alcoholic drink, are more likely to experience early intoxication, and are at a heightened risk for the onset of an alcohol use disorder.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 69 publications
1
15
0
2
Order By: Relevance
“…This is in line with the self-medication theory whereby substances are used to mediate mood disorders or innate reward deficiencies (9). Also, adolescents with high stress and amygdala reactivity are more likely to consume a full standard alcoholic drink, are more likely to experience early intoxication, and are at a heightened risk for the onset of an alcohol use disorder (57). In line with this, anhedonia can be hypothesized as a vulnerability trait for early substance use trajectories and subsequent increase of DUS risk.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the self-medication theory whereby substances are used to mediate mood disorders or innate reward deficiencies (9). Also, adolescents with high stress and amygdala reactivity are more likely to consume a full standard alcoholic drink, are more likely to experience early intoxication, and are at a heightened risk for the onset of an alcohol use disorder (57). In line with this, anhedonia can be hypothesized as a vulnerability trait for early substance use trajectories and subsequent increase of DUS risk.…”
Section: Discussionmentioning
confidence: 99%
“…Oshri et al [ 144 ] showed that ELS-related changes in AMG volume were associated with increased anxiety, depressive symptoms, and alcohol use. Heightened threat-related AMG reactivity has been shown to predict internalizing symptoms [ 145 ] and risks for alcohol use disorder [ 146 , 147 ]. In contrast, ELS has been associated with reduced mPFC volume [ 148 , 149 ] and lower mPFC activation during both resting state and cognitive tasks [ 150 , 151 , 152 ].…”
Section: Role Of Mesocorticolimbic Emotion Processing Circuits In Els and Oudmentioning
confidence: 99%
“…In line with animal models demonstrating that neuroplastic changes in the striatum mediate exaggerated salience to drug cues at the expense of natural rewards and habitual responses to cues repeatedly paired with the drug (Robbins, Ersche, & Everitt, 2008), exaggerated striatal drug cue reactivity and blunted striatal processing of nondrug rewards has been demonstrated in functional MRI studies in human drug users with regular and addictive use of different substances (Chase, Eickhoff, Laird, & Hogarth, 2011; Kühn & Gallinat, 2011; Vollstädt‐Klein et al, 2010; Zhou et al, 2019; Zimmermann et al, 2019). However, despite convergent evidence for striatal maladaptations across different substance use disorders, substance‐specific predisposing factors (Becker et al, 2015; Cheng et al, 2019; Elsayed et al, 2018; Zilberman, Yadid, Efrati, & Rassovsky, 2019) and addiction‐related alterations have been increasingly recognized, such that frontal regions have been found to be differentially impacted by stimulant or opioid use (Badiani, Belin, Epstein, Calu, & Shaham, 2011) and neurocognitive deficits in domains associated with frontostriatal circuits such as inhibitory control and cognitive flexibility have been found to be differentially impacted by alcohol, stimulants, and cannabis (Fernández‐Serrano, Pérez‐García, & Verdejo‐García, 2011; Smith, Mattick, Jamadar, & Iredale, 2014). Further evidence for substance use disorder‐specific brain alterations comes from a recent qualitative review suggesting that different addictions may be associated with alterations in distinct brain systems and particularly alterations in frontal regions appear to be substance‐specific (Zilberman, Lavidor, Yadid, & Rassovsky, 2019).…”
Section: Introductionmentioning
confidence: 99%